Mobile applications for teaching and learning Arabic braille - Nik Mohd Rahimi, Nik Azimah Zainab; Mohamad Hanif, Noor Hazrin Hany; Janin, Zuriati (IEEE, 2019)
Nowadays, the literacy rate of the visually impaired people is decreasing and has become a big concern because reading is the main source of information. However, lack of skilled teachers is the main issue that restricts the learning of braille code for blind people. Most of the braille modules available in the market today are only catered for languages that utilize roman alphabets. This made it impossible for users to learn braille in languages with different alphabets or characters. The aim of this Arabic Braille Module is to help the visually impaired people to learn on reading and writing Arabic characters in braille code. It is also to facilitate the teachers in demonstrating the braille code in teaching process. A portable Arabic braille module is to be designed using miniature solenoids with Arduino Uno as microcontroller. In this work, simulation and experiments have been conducted to study the capability of the module to generate output according to specific input provided from teaching panel designed in mobile applications. At this current stage, the output of the system is a 3-by-2 array of LEDs to represent the raising dots of the braille codes. Hopefully with the invention of this Arabic Braille Module will encourage the visually impaired people to learn Arabic and eventually reading Quran in braille.